Antidiabetic, antioxidant, and therapeutic effects of Salvia balansae leaf and stem extracts on sexual function in diabetic male rats - Souidi Sendous W.; Belhocine Mansouria; Feknous Ines; Bensouici Chawki; Sitayeb Tayeb; Dahou Abdelkader A. (Archives of Biological Sciences)
This study investigates the in vitro antioxidant and antidiabetic effects, and in vivo the pro-sexual activities of aqueous extracts from Salvia balansae leaves (LAE) and stems (SAE) in streptozotocin (STZ)-induced diabetic male rats. The total polyphenol and flavonoid contents, as well as the antioxidant activity of the extracts, were assessed using the DPPH radical scavenging and FRAP assays. Following the induction of diabetes by intraperitoneal injection of STZ (40 mg/kg), diabetic rats received 200 mg/kg of LAE/SAE. Acute oral toxicity, glycemic levels, sexual behavior parameters, and serum testosterone levels were assessed. S. balansae extracts exhibited high levels of total polyphenols and flavonoids, reflecting an antioxidant capacity. Acute toxicity tests confirmed a high safety margin, with no observed toxicity at doses up to 2 g/ kg. In diabetic rats, LAE and SAE administration reduced hyperglycemia and enhanced sexual function, as evidenced by increased male-female interaction frequency, decreased latency times, and elevated serum testosterone levels, pointing to an aphrodisiac effect. This work demonstrates the therapeutic potential of S. balansae leaf and stem extracts in improving reproductive function in diabetic rats, potentially through its antioxidant, antihyperglycemic and aphrodisiac properties.